Trends of Cyclone Characteristics in the Arctic and Their Patterns From Different Reanalysis Data. Issue 5 (14th March 2018) - Zahn, Matthias; Akperov, Mirseid; Rinke, Annette; Feser, Frauke; Mokhov, Igor I.
Abstract: Cyclones in the Arctic are detected and tracked in four different reanalysis data sets from 1981 to 2010. In great detail the spatial and seasonal patterns of changes are scrutinized with regards to their frequencies, depths, and sizes. We find common spatial patterns for their occurrences, with centers of main activity over the seas in winter, and more activity over land and over the North Pole in summer. The deep cyclones are more frequent in winter, and the number of weak cyclones peaks in summer. Overall, we find a good agreement of our tracking results across the different reanalyses. Regarding the frequency changes, we find strong decreases in the Barents Sea and along the Russian coast toward the North Pole and increases over most of the central Arctic Ocean and toward the Pacific in winter. Areas of increasing and decreasing frequencies are of similar size in winter. In summer there is a longish region of increase from the Laptev Sea toward Greenland, over the Canadian archipelago, and over some smaller regions west of Novaya Zemlya and over the Russia. The larger part of the Arctic experiences a frequency decrease. All the summer changes are found statistically unrelated to the winter patterns. In addition, the frequency changes are found unrelated to changes in cyclone depth and size. There is generally good agreement across the different reanalyses in the spatial patterns of the trend sign. However, the magnitudes of changes in a particular region may strongly differ across the data. Key Points: Spatial patterns of Arctic cyclone trends are similar across different reanalysis products Frequency changes of Arctic cyclones are unrelated to changes in their intensity and size Deep Arctic cyclones and all Arctic cyclones take a reversed course across the year